The Exception as a Challenge to Philip Pettit’s Republican Theory - Camargo, Ricardo (Revista de Filosofía, 2024)
Following the paradigmatic proposal formulated by Giorgio Agamben regarding the state of exception as a constitutive device of the state legal order, this work critically confronts one of the basic premise that has always haunted the republican theory, both in its aspects linked to the works of Hannah Arendt like those of Phillip Pettit, and which is usually presented as an inclusive question, namely: how to make politics and freedom possible not only for some but for all. We argue that Agamben’s proposal establishes a foothold that forces republicanism to rethink its conditions of possibility in a more radically critical way than it has usually done – a radicality that could even force it to go beyond the state form that for centuries has accompanied the promise of Republican inclusion.